2011
DOI: 10.1186/1756-0500-4-206
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three malignancy risk indices and CA-125 in the preoperative evaluation of patients with pelvic masses

Abstract: BackgroundPatients with pelvic mass are the most referred patients to gynecologist. The aim of this study was to evaluate the ability of three malignancy risk indices (RMI 1, RMI 2 and RMI 3) and CA-125 to discriminate a benign from a malignant pelvic mass in our region (North of Iran).MethodsThis retrospective study was performed on 182 women with pelvic masses referred to Yahyanejad Hospital from 2007 to 2009. Ultrasound scans were scored as one point for each of the following characteristics: multilocular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…However, in our study, we found higher specificity (91.0%) but lower sensitivity (75.0%) for RMI-4 as compared to previous reports. Many studies evaluating RMI scales in Asian and Pacific countries have reported different cut-off values compared to those originally reported by the investigators who proposed these indexes at the first place (Lou et al, 2010;Ashrafgangooei and Rezaeezadeh, 2011;Bouzari et al, 2011). On the other hand, according to the report by van den Akker et al from Holland, a cut-off value of 200 for RMI-3 and 450 for RMI-4 showed the best performance and yielded success rates similar to that reported by the original investigators (Tingulstad et al, 1999;Yamamoto et al, 2009;van den Akker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, we found higher specificity (91.0%) but lower sensitivity (75.0%) for RMI-4 as compared to previous reports. Many studies evaluating RMI scales in Asian and Pacific countries have reported different cut-off values compared to those originally reported by the investigators who proposed these indexes at the first place (Lou et al, 2010;Ashrafgangooei and Rezaeezadeh, 2011;Bouzari et al, 2011). On the other hand, according to the report by van den Akker et al from Holland, a cut-off value of 200 for RMI-3 and 450 for RMI-4 showed the best performance and yielded success rates similar to that reported by the original investigators (Tingulstad et al, 1999;Yamamoto et al, 2009;van den Akker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Ashrafgangooei and Rezaeezadeh (2011) reported a cutoff value of 238 for RMI-1 to be performing better in their population. Likewise, Bouzari et al (2011) reported a cut-off value of 265 for RMI-1 and 3, and 355 for RMI-2 in their study conducted in Iran which is Turkey's neighboring country.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumours were common in postmenopausal women. Similarly in studies conducted by MA Shuiqing et al (10) , Jung Woo Park et al (8) and Zinatossada Bouzari et al (11) observed overall incidence of ovarian masses was less in postmenopausal patients. Earlier menstrual score alone was used in predicting malignancy.…”
Section: Menstrual Historymentioning
confidence: 51%
“…In the present study, the cut off level of RMI is taken as 250.This scoring was more closer to Zinatossadat Bouzari et al, 13 who used 265 as cut off .In the present study sensitivity, specificity, PPV & NPV of RMI was found to be 85.71%, 85.07%, 75%, 91.93% respectively. Similar statistical significance was observed by Ismail Kestane et al 14 and Zinatossadat Bouzari et al 13 In the present study, out of 102 clinically diagnosed ovarian masses, 7 cases were noted with lower RMI (i.e.<250 ) which turned out to be malignant on histopathology. This gave the false negative rate of 11.11%.…”
Section: Discussionmentioning
confidence: 65%